Insured loss inflation: How natural catastrophes affect reconstruction costs - David Döhrmann; Marc Gürtler; Martin Hibbeln (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2013)
In the aftermath of a natural catastrophe, there is increased demand for skilled reconstruction labor, which leads to significant increases in reconstruction labor wages and hence insured losses. Such inflation effects are known as 'Demand Surge' effects. It is important for insurance companies to properly account for these effects when calculating insurance premiums and determining economic capital. We propose an approach to quantifying the Demand Surge effect and present an econometric model for the effect that is based on 191 catastrophe events in the United States. Our model explains more than 75% of the variance of the Demand Surge effect and is thus able to identify the key drivers of the phenomenon.
Keywords: G22; J23; J31; Q54; R23; 330; Demand Surge; Natural Catastrophes; Reconstruction; Insured Losses